The Role of Service Quality and Price in Enhancing Customer Satisfaction Using the SPSS Regression Method - Purwanto, Purwanto; Yulfiswandi, Yulfiswandi; Donal Mon, Muhammad (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This study aims to examine the impact reliability, responsiveness, assurance, empathy, tangible and price on satisfaction. This study investigates how the service provided by the management of Tanjung Uban Ferry Port. This study uses a quantitative methodology, collecting firsthand data through the use of questionnaires and multiple linear regression techniques. According to Roscoe's recommendation, the optimal sample size is 250 respondents; however, this study uses information from 311 respondents who use Tanjung Uban Ferry Port. to provide more representative and comprehensive results. reliability, responsiveness, assurance, empathy, tangibles and price are independent variables while customer satisfaction is the dependent variable. This study uses SPSS software. The statistical analysis confirms that responsiveness, assurance, empathy, tangibility, and price all have a meaningful and positive impact on customer satisfaction. However, the reliability element does not affect customer satisfaction. These findings improve current research on the correlation between service quality, price, and customer satisfaction by introducing an alternative model that explains this relationship. Referring to the research results For the managers of Tanjung Uban Ferry Port, referring to the research findings, it is important to maintain and improve physical facilities, especially infrastructure that has a direct impact on passengers, such as waiting rooms, pedestrian facilities, and parking facilities. These aspects are directly seen and experienced by passengers.